(untitled) (Research, Society and Development, 2025)
ADPKD causes kidney cysts, leading to an increase in total renal volume (TRV) and eventually evolves to chronic renal failure due to declining glomerular filtration rate (GFR). Mutations in polycystin genes alter calcium influx and cAMP production, resulting in cyst formation under the influence of vasopressin. Tolvaptan, a vasopressin receptor inhibitor, aims to slow renal function decline and improve quality of life. The review’s objective is to demonstrate the effects of Tolvaptan in ADPKD, highlighting its efficacy and impact on quality of life and progression to kidney failure. Data were collected in BVS, PubMed and New England Journal of Medicine, yielding 446 results. After manual screening in Excel, 41 studies remained, including clinical trials, retrospective analyses and cohorts, without language restrictions. Results indicated that Tolvaptan reduced cyst proliferation, limited TRV expansion by 2.6%, delayed GFR decline by 10 ml/min/1.73m² over 3 years and extended time to kidney failure nearly by 8.5 years. Side effects included up to a 138% increase in urine volume, elevated liver enzymes and creatine kinase levels. Monthly monitoring during the initial 18 months is crucial and temporary drug suspension reverses adverse effects in cases of hepatic decompensation. Overall, Tolvaptan appears effective in treating ADPKD, significantly prolonging renal lifespan. Despite side effects, the drug is safe and effective when appropriately monitored.